Distress Prediction in Transportation-Logistics: Integrating Financial and Governance Factors - Sri Sulasmiyati; Annisa Maghfirah (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
This study examines the influence of financial ratios and corporate governance mechanisms on financial distress in transportation and logistics companies listed on the Indonesia Stock Exchange over the 2019–2023 period. Financial performance is proxied by the Current Ratio (CR) for liquidity, Return on Assets (ROA) for profitability, and Debt-to-Equity Ratio (DER) for leverage, while Corporate Governance (CG) is measured through the proportion of independent commissioners and audit committee size. Financial distress is assessed using the Altman Z-Score. A purposive sampling technique yielded a final sample of 12 companies, generating 60 firm-year observations. Data were analyzed using descriptive statistics and inferential methods, including classical assumption tests, multiple linear regression, coefficient of determination, F-test, and t-test, with IBM SPSS Statistics version 26 employed for data processing. The empirical findings reveal that the five independent variables, when considered jointly, exert a statistically significant effect on financial distress. Individually, CR, ROA, DER, and the proportion of independent commissioners demonstrate significant partial effects, whereas audit committee size does not exhibit a statistically significant influence. By integrating financial ratios with corporate governance mechanisms, this study provides novel evidence on distress prediction in Indonesia’s transportation and logistics sector, offering theoretical enrichment to the literature on financial distress and practical guidance for managers and regulators in strengthening early‑warning systems.